Pengaruh Aplikasi Mikoriza dan Bahan Pembenah terhadap Sifat Kimia dan Serapan Fosfor di Tanah Pasir - Aktavia Herawati; Jauhari Syamsiyah; Mujiyo Mujiyo; Mapan Rochmadtulloh (Fakultas Pertanian Universitas Padjadjaran, 2020)
Sandy soil has limitations factor in supporting plant growth such as low soil organic carbon (SOC), cation exchange capacity (CEC), macro-micro nutrient content, water retention capacity, and high permeability rate. To improve soil conditions, it can be done by adding mycorrhizae and soil amendments. This study aimed to determine the effect of mycorrhizae application and soil amendments on the P availability and P uptake of plants in sandy soil. The research was conducted in a greenhouse of Agricultural Faculty, Sebelas Maret University. Used a completely randomized design consisting of 2 factors. The first factor was mycorrhizae with 2 levels, namely without mycorrhizae (M0) and mycorrhizae with 6 spores/plants (M1). The second factor was soil amendments; without amendment (P0), cow manure 60 tons/ha (P1), rock phosphate 150 kg/ha (P2), and combination of cow manure 60 tons/ha and rock phosphate 150 kg/ha (P3). The results showed that the application of mycorrhizae and soil amendments significantly increased available P, SOC, CEC, P concentration, and P uptake. Interaction of mycorrhizae 6 spores/plant and rock phosphate 150 kg/ha was able to increase the availability of soil P up to 12.8 times, plant tissue P concentration up to 1.4 times, and P uptake up to 2.27 times compared to the control. Application of mycorrhizae 6 spores/plant and cow manure of 60 tons/ha gave the best results on SOC and mycorrhizae with a combination of cow manure and rock phosphate gave the best results on CEC.